Grafting Snake Melon [Cucumis melo L. subsp. melo Var. flexuosus (L.) Naudin] in Organic Farming: Effects on Agronomic Performance; Resistance to Pathogens; Sugar, Acid, and VOC Profiles; and Consumer Acceptance - Flores-León, Alejandro; García-Martínez, Santiago; González, Vicente; Garcés-Claver, Ana; Martí, Raúl; Julián, Carmen; Sifres, Alicia; Pérez-de-Castro, Ana; Díez, María José; López, Carmelo; Ferriol, María; Gisbert, Carmina; et al. (Frontiers in Plant Science, 2021)
The performance of snake melon [Cucumis melo var. flexuosus (L.)] in organic farming was studied under high biotic and salt stress conditions. Soilborne diseases (mainly caused by Macrophomina phaseolina and Neocosmospora falciformis), combined with virus incidence [Watermelon mosaic virus (WMV), Zucchini yellow mosaic virus (ZYMV), and Tomato leaf curl New Delhi virus (ToLCNDV)] and Podosphaera xanthii attacks, reduced yield by more than 50%. Snake melon susceptibility to M. phaseolina and Monosporascus cannonballus was proved in pathogenicity tests, while it showed some degree of resistance to Neocosmospora keratoplastica and N. falciformis. On the contrary, salt stress had a minor impact, although a synergic effect was detected: yield losses caused by biotic stress increased dramatically when combined with salt stress. Under biotic stress, grafting onto the melon F1Pat81 and wild Cucumis rootstocks consistently reduced plant mortality in different agroecological conditions, with a better performance compared to classic Cucurbita commercial hybrids. Yield was even improved under saline conditions in grafted plants. A negative effect was detected, though, on consumer acceptability, especially with the use of Cucurbita rootstocks. Cucumis F1Pat81 rootstock minimized this side effect, which was probably related to changes in the profile of sugars, acids, and volatiles. Grafting affected sugars and organic acid contents, with this effect being more accentuated with the use of Cucurbita rootstocks than with Cucumis. In fact, the latter had a higher impact on the volatile organic compound profile than on sugar and acid profile, which may have resulted in a lower effect on consumer perception. The use of Cucumis rootstocks seems to be a strategy to enable organic farming production of snake melon targeted to high-quality markets in order to promote the cultivation of this neglected crop.